Percutaneous Intracoronary Delivery of Plasma Extracellular Vesicles Protects the Myocardium Against Ischemia-Reperfusion Injury in Canis. Issue 5 (November 2021) - Wang, Hongyun; Maimaitiaili, Rusitanmujiang; Yao, Jianhua; Xie, Yuling; Qiang, Sujing; Hu, Fan; Li, Xiang; Shi, Chao; Jia, Peng; Yang, Haotian; Wei, Meng; Zhao, Juan; et al.
Abstract : Plasma circulating extracellular vesicles (EVs) have been utilized as a potential therapeutic strategy to treat ischemic disease through intramyocardial injection (efficient but invasive) or tail vein injection (noninvasive but low cardiac retention). An effective and noninvasive delivery of EVs for future clinical use is necessary. The large animal (canine) model was complemented with a murine ischemia-reperfusion injury (IRI) model, as well as H9 human embryonic stem cell–induced cardiomyocytes or neonatal rat cardiomyocytes to investigate the effective delivery method and the role of plasma EVs in the IRI model. We further determine the crucial molecule within EVs that confers the cardioprotective role in vivo and in vitro and investigate the efficiency of CHP (cardiac homing peptide)-linked EVs in alleviating IRI. D-SPECT imaging showed that percutaneous intracoronary delivery of EVs reduced infarct extent in dogs. CHP-EVs further reduced IRI-induced cardiomyocyte apoptosis in mice and neonatal rat cardiomyocytes. Mechanistically, administration of EVs by percutaneous intracoronary delivery (in dog) and myocardial injection (in mice) just before reperfusion reduced infarct size of IRI by increasing miR-486 levels. miR-486–deleted EVs exacerbated oxygen-glucose deprivation/reoxygenation–induced human embryonic stem cell–induced cardiomyocytes and neonatal rat cardiomyocyte apoptosis. EV-miR-486 inhibited the PTEN (phosphatase and tensin homolog deleted on chromosome ten) expression and then promoted AKT (protein kinase B) activation in human embryonic stem cell–induced cardiomyocytes and neonatal rat cardiomyocytes. In conclusion, plasma-derived EVs convey miR-486 to the myocardium and attenuated IRI-induced infarction and cardiomyocyte apoptosis. CHP strategy was effective to improve cardiac retention of EVs in mice (in vivo) and dogs (ex vivo). Abstract : Supplemental Digital Content is available in the text.